108k views
1 vote
Anyone know how to solve this??

Anyone know how to solve this??-example-1
User Refaat
by
5.5k points

1 Answer

4 votes


Given : ((x^(2)/(5))^9\;.\;(x^(-4)/(15)))/(x^(1)/(3))


\implies {(x^(18)/(5))\;.\; (x^(-4)/(15))}\;.\;(x^(-1)/(3))


\implies x^(^(18)/(5) ^-^(4)/(15)^-^(1)/(3)^)


\implies x^(^(^(54 - 4)/(15)^)^-^(1)/(3)^) = x^(^(^(50)/(15)^)^-^(1)/(3)^) = x^(^(^(10)/(3)^)^-^(1)/(3)^) = x^(^(9)/(3)^) = x^3


\implies x^k = x^3


\implies k = 3

User Jimena
by
5.6k points